Toxoplasma gondii in urban and rural bats from São Paulo state, Brazil - França, Danilo Alves de [UNESP]; Menozzi, Benedito Donizete [UNESP]; Langoni, Helio [UNESP] (Elsevier, 2025)
The aim of this study was to detect Toxoplasma gondii in organs of urban and rural bats from 17 cities in São Paulo, Brazil. A total of 203 bats, including insectivorous, frugivorous and hematophagous species, were collected from urban and rural areas between 2020 and 2022. DNA was extracted from heart and kidney samples and analyzed using real-time PCR as a screening method, followed by conventional PCR to obtain a viable product for genetic sequencing and phylogenetic analysis. In total, 14.8 % of the samples were positive in real-time PCR and 9.4 % were sequenced. Phylogenetic analysis indicated low genetic proximity between the sequences detected in bats and those associated with domestic species, suggesting that bats may be exposed to specific sources of infection in the wild. The lack of statistical association with variables such as feeding habits and type of shelter suggests that multiple environmental factors contribute to infection. This study emphasizes the potential role of bats as intermediate hosts in the T. gondii transmission cycle, acting as environmental sentinels and possibly as ecological vectors. These findings contribute to understanding the distribution of T. gondii in bat populations and its implications for public health, especially in vulnerable communities, where poor sanitation and close contact with farm animals increase the risk of zoonotic transmission.
Keywords: Chiroptera; PCR; Public health; Surveillance; Zoonoses